تضافر النحو والبلاغة في تفسير التراكيب الإسنادية الإنشائية الطلبية –المعلقات العشر أنموذجا - (مجلة إحالات, 2025)
العلاقة بين النحو والبلاغة علاقة قديمة وطيدة، ولا يستطيع أحد أن ينكرها، أو أن ينكر فضل النحويين على البلاغيين ،وفضل البلاغيين على النحويين ، لذلك في أثناء دراستنا للتراكيب الإسنادية ، وحتى نحقق الهدف لأجل فهمها لزام علينا أن نزاوج بين النحو والبلاغة، فسؤال البلاغة ينعطف على سؤال النحو من خلال سؤال المعنى. والدلالة تتجلى أولا في آلية الارتباط بين الألفاظ المتوالية نسقيا في الكلام المنظوم، وفي التركيب الإسنادي الواحد، وهذا ما يقدمه الدرس النحوي، لتأتي البلاغة بعد ذلك فتقدم الأغراض التي ينزاح إليها كل تركيب، كأغراض الحذف، والإطناب، والإظهار والإضمار....ولأن بنية التراكيب النحوية بكل ظواهرها المعهودة في العربية عادة ما يخضع التصرف فيها لنوعية النص الأدبي، ولمّا كان يجوز للشاعر ما لا يجوز لغيره، اخترنا مدونة المعلقات العشر؛ لغناها بالتراكيب الإساندية الجميلة، بل الرائعة، وأحيانا الصعبة والغريبة ، وهذا ما حاولنا الوقوف عليه في هذا المقال، وخصصنا الكلام فيه عن التراكيب الإسنادية الإنشائية الطلبية،ودلالاتها البلاغية، كالاستفهام، والتمني، والنهي، والدعاء. الكلمات المفتاحية: التركيب – الإسناد – الدلالة البلاغية – النظم – النمط – الإنشاء. Abstract: Between the syntax and the rhetoric an ancient and close relation, and is neither denied by any one, nor by the owing of structuralisms on the rhetoricians; that’s why within our study of the predicative structures, and in order that we achieve the purpose for our understanding, it was obligatory to combine the syntax and the rhetoric, then the question of the rhetoric turns on the question of syntax through the question of lexis. The semantics is first raising in the mechanism of the linkage between the frequent arrays expressions in a rhymed speech, into a single predicative structure; this is what the syntactic course yielded. Then comes the rhetoric to give us the aims for which each texture is exodus, like: the aims of the cancellation, the prolixity, the manifestation and the atrophy … and because the building of the syntactical structures with all their usual appearances in the Arabic is usually submitted to the behavior of the literary text quality, and as it allows the poet what is not permissible for others, we chosen the blog of the Ten Pendants for its richness in diversified predicative structures, and the beautiful, yet the wonderful and sometimes of the difficult and the strange ones, all that we tried to stand on it in this article where we specified the speech about the required constructive structural predicative, and their rhetorical significances such as: the interrogation, and the wishful, and the banning, and the supplication.